Plyometric training and the adolescent athlete - Popovic, N. (Journal of Australian Strength and Conditioning, 2016)
Strength and conditioning programs contain various forms of exercise philosophies that assist in physical improvement. Young athletes that are actively involved in sports may benefit from a plyometric program. A developmental plyometric program for the adolescent athlete should be evidence based and in conjunction with a specific strength based program. As a result biomechanical technique could be improved.